Epidemiology of Suicide by Hanging in Fars Province, Iran (2011-2019): A Population-based Cross-sectional Study - Leila Moftakhar; Alireza Mirahmadizadeh; Sanaz Amiri; Fariba Rezaei; Habibollah Azarbakhsh (Korean Society for Preventive Medicine, 2023)
Objectives Hanging is a common method of attempted suicide. This study investigated the epidemiological profile of attempted and completed suicides by hanging in southern Iran. Methods This cross-sectional study was performed on 1167 suicide attempts by hanging between 2011 and 2019. All data related to suicide attempts by hanging were collected from the Fars Suicide Surveillance System. The trends in suicide cases and the mean age of attempted and completed suicides were plotted. The chi-square test was used to identify suicide-related factors. Crude rates of incidence, mortality, and standardized fatality during the study period were calculated. Finally, logistic regression was used to identify the predictors of death in individuals who attempted suicide. Results The mean age of those who attempted suicide was 33.21±16.82 years; the majority were male (80.5%). The rate of attempted and completed suicide by hanging were 3.50 and 2.79 per 100 000 people, respectively. The case-fatality rate was calculated as 79.34%. The results of our study indicated an increasing trend in suicide attempts by hanging. The likelihood of death was 2.28 times higher in individuals with a previous history of suicide attempts and 1.85 times higher in those with a psychological disorder. Conclusions The findings of this study suggest an increasing trend in attempted and completed suicide by hanging, especially among individuals with a history of suicide attempts and psychological disorders. It is necessary to take action to reduce the rate of suicide attempts and identify the underlying causes of suicide attempts by hanging.